POSTULAT KESEJAJARAN EUCLID DALAM TINJAUAN SEJARAH - Agung Prabowo (Universitas Jenderal Soedirman, 2009)
This paper tracks the history of Euclid’s fifth postulate or parallel postulate. It is a long term postulate and dificult to be understood, and can evoke misunderstanding. Moreover, this postulate had evoked discourse among mathematicians about its dependency with other postulates for a long time untill the 19th century. The discourse related to assuredness of mathematician after Euclid’s era is whether or not Euclid’s fifth postulate can be deduced from other four postulates. But, the discourse became precisely a cause of finding of new geometry system, called non-Euclide geometry.